2019
DOI: 10.1177/1069072719830293
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Initial Validation of the Work Orientation Questionnaire

Abstract: The goal of the present research was to develop a model of work meaning, consisting of five orientations: job (financial compensation), career (advancement and influence), calling (prosocial duty), social embeddedness (belongingness), and busyness (filling idle time with activities). Two versions of the Work Orientation Questionnaire (WOQ), which measures these five orientations, were developed—for young adults and for working adults. Study 1 describes the development of the WOQ and psychometric properties for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 41 publications
4
48
0
Order By: Relevance
“…Third, some university students may have a continuously low calling during the transition from university to work. Research suggests that people differ in their levels of calling and some students might not have a strong sense of calling to begin with, possibly because they have other orientations towards work, such as a job or career orientation which emphasize more on financial rewards or career advancement (Willner et al, 2019; Wrzesniewski et al, 1997). When entering to work roles, some individuals may not reshape their identity and thereby may sustain their low levels of calling.…”
Section: Introductionmentioning
confidence: 99%
“…Third, some university students may have a continuously low calling during the transition from university to work. Research suggests that people differ in their levels of calling and some students might not have a strong sense of calling to begin with, possibly because they have other orientations towards work, such as a job or career orientation which emphasize more on financial rewards or career advancement (Willner et al, 2019; Wrzesniewski et al, 1997). When entering to work roles, some individuals may not reshape their identity and thereby may sustain their low levels of calling.…”
Section: Introductionmentioning
confidence: 99%
“…The term “ of ” generally refers to what something signifies to one individual. Hence, using this terminology indicates the cognitive process by which an individual interprets and attaches a meaning to their work ( Wrzesniewski, 2003 ; Willner et al, 2019 ), although it can have a different value ( Lepisto and Pratt, 2017 ) pertaining to when work per se is at issue ( Schnell et al, 2013 ). Meaningful work, meaningfulness, and meaning in/at refer to significance, subjective experience, and perception of the value of work ( Lips-Wiersma and Morris, 2009 ; Rosso et al, 2010 ; Schnell et al, 2013 ; Allan et al, 2019 ).…”
Section: Meaningful Work and Timementioning
confidence: 99%
“…In the current context of temporary and difficult jobs and socio-political changes, some authors hypothesized that individuals can find a meaning crafting their experience to gain an experience of meaningful work ( Wrzesniewski and Dutton, 2001 ; Rosso et al, 2010 ; Berg et al, 2013 ; Mitra and Buzzanell, 2017 ). Existing literature reports how the economy and society structure jobs and organizations in a top-down manner, with a focus on the stable characteristics of labor conditions that highlight the need for future research on the experience of meaningful work within a more substantial temporal lens ( MOW International Research Team, 1987 ; Willner et al, 2019 ). As noted by Thompson (2019) , the literature in the field mostly overlooks the relevance of macro-aspects of the institutions on shaping the opportunities for meaningful work.…”
Section: Toward the Dual Nature Of Meaningful Workmentioning
confidence: 99%
“…This is because research shows that combining autonomous and controlled motivation is most beneficial to positive workplace outcomes (Howard, Gagné, Morin, & Van den Broeck, 2016). Finally, university students with undeveloped calling may exhibit less successful transition outcomes than those with other types of calling because research has found that individuals with a job or career orientation have lower job/work satisfaction than employees a calling orientation (Wrzesniewski et al, 1997;Willner, Lipshits-Braziler, & Gati, 2020).…”
Section: Outcomes Of Calling Profiles In Successful Transition To Workmentioning
confidence: 99%